PENGEMBANGAN BAHAN AJAR BERBASIS KEARIFAN LOKAL KOTA PONTIANAK MATERI INDONESIAKU KAYA BUDAYA KELAS IV SDN 14 PONTIANAK SELATAN - Aisyah, Siti; Halidjah, Siti; Ghasya, Dyoty Auliya Vilda (Universitas Tanjungpura, 2026)
This study aims to produce teaching materials based on the local wisdom of Pontianak City for the IPAS subject, specifically Social Studies, on the topic Indonesiaku Kaya Budaya for fourth-grade students at SD Negeri 14 Pontianak Selatan. These materials are designed to support the learning process in the Merdeka Curriculum. The research method used is Research and Development (R&D) by adapting the 4-D model. The research sample includes two validators: the material aspect received an average score of 3.35 with the criteria of “Highly Feasible”, for the developed teaching materials based on the local wisdom of Pontianak City. These results are supported by development trial activities, where teacher responses obtanined a percentage score of 100% with the criteria of “Excellent”, small-scale student responses reached 80.5% with the criteria of “Excellent”, and large-scale student responses reached 79.98% with the criteria of “Excellent”. The findings indicate that fourth-grade students are interested in and understand the teaching materials based on the local wisdom of Pontianak City, as they are designed to align with the local culture of Pontianak. Therefore, it can be conclude that the teaching materials based on the local wisdom of Pontianak City are suitable for use in he learning process.